Congestion in heart failure: a circulating biomarker‐based perspective. A review from the Biomarkers Working Group of the Heart Failure Association, European Society of Cardiology. (7th September 2022) - Núñez, Julio; de la Espriella, Rafael; Rossignol, Patrick; Voors, Adriaan A.; Mullens, Wilfried; Metra, Marco; Chioncel, Ovidiu; Januzzi, James L.; Mueller, Christian; Richards, A. Mark; de Boer, Rudolf A.; Thum, Thomas; et al.
Abstract: Congestion is a cardinal sign of heart failure (HF). In the past, it was seen as a homogeneous epiphenomenon that identified patients with advanced HF. However, current evidence shows that congestion in HF varies in quantity and distribution. This updated view advocates for a congestive‐driven classification of HF according to onset (acute vs. chronic), regional distribution (systemic vs. pulmonary), compartment of distribution (intravascular vs. extravascular), and clinical vs. subclinical. Thus, this review will focus on the utility of circulating biomarkers for assessing and managing the different fluid overload phenotypes. This discussion focused on the clinical utility of the natriuretic peptides, carbohydrate antigen 125 (also called mucin 16), bio‐adrenomedullin and mid‐regional pro‐adrenomedullin, ST2 (also known as interleukin‐1 receptor‐like 1), cluster of differentiation 146, troponin, C‐terminal pro‐endothelin‐1, and parameters of haemoconcentration. The utility of circulation biomarkers on top of clinical evaluation, haemodynamics, and imaging needs to be better determined by dedicated studies. Some multiparametric frameworks in which these tools contribute to management are proposed. Abstract : Schematic summary of circulating surrogate biomarkers of congestion. bioADM, biologically active adrenomedullin; BNP, B‐type natriuretic peptide; CA125, carbohydrate antigen 125; CD146, cluster of differentiation 146; ET‐1, endothelin‐1; ICAM‐1, intercellular adhesion molecule‐1; IL, interleukin; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide; TNF‐α, tumour necrosis factor alpha; VCAM‐1, vascular cell adhesion molecule‐1.